1967
DOI: 10.1002/bip.1967.360050207
|View full text |Cite
|
Sign up to set email alerts
|

Stability of helical polyamino acids in solution at high temperatures

Abstract: SynopsisOptical rotatory dispersion studies have been carried out at, temperatures up to 150°C. on poly(ybenzy1 Lgliitamate) in a-chloronaphthalene and N-methylcaprolactam, and on poly-6-carbobeiixoxy-L-lysine, poly-6-carbobenzoxy-Lo1 nithine, and poly(bg1utamic acid) in N-methylacetamide. The h3offittrYang -bo values were large in all cases, buts significant decreases in -bo were observed a t the upper temperature limits of the stiidy suggesting that a transition region was being entered. Polymer degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1969
1969
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…It is confirmed from the potentiometric titration behavior 15 and the previous studies [11][12][13] that these two samples are in helical states.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…It is confirmed from the potentiometric titration behavior 15 and the previous studies [11][12][13] that these two samples are in helical states.…”
Section: Methodssupporting
confidence: 86%
“…This conclusion is compatible with the suggestions made by Holtzer et al 13 and others. 11,12 I am indebted to Professor M. Nagasawa of Toyota Technological Institute for valuable discussions.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the thermal stability of the helical conformation of polyamino acids in various solvents indicated an exceptional stability of the L-PGA helix in NlMA. 7 The rotatory dispersion data showed that a t temperatures up to 160°C the helical content had not decreased appreciably. The inability to observe a thermally induced transition obviated the possibility of learning anything about the thermodynamics of the process.…”
mentioning
confidence: 98%
“…If one could observe the transition, one could estimate the effect of side chains of PBLG on the stability of the helix. On the other hand, if one could confirm the helical conformation of PBLG at high temperatures, it would give further information with respect to the stability of the PBLG helix.Franzen, et al, 3 have investigated the conformation of PBLG at high temperatures. They measured the ORD of PBLG in chloronaphthalene up to 168°C and in N-methyl caprolactame up to 157"C, and observed a significant decrease in the Moffitt-Yang b0 values at the upper temperature limits of the study.…”
mentioning
confidence: 99%